Religious Establishment According to a Substantive Ethics of Political Justice - Carvalho, Tarcisio Amorim (REVER: Revista de Estudos da Religião, 2018)
Contemporary political theorists often disagree on whether or not religious establishment is justified in liberal states, even when its existence does not constitute a hindrance to the basic rights of citizens. In this article, I contend that religious established does not raise issues of democratic legitimacy, by showing that political frameworks of justice are entangled with substantive conceptions of the good and ethical forms of life. Then, drawing on Jürgen Habermas’s latest works on the relationship between religion and the public sphere, and Maeve Cooke’s readings thereof, I argue that religious symbols can contribute to the creation of meaningful imaginaries that inform moral norms and principles of justice. After this, I recall Axel Honneth’s conception of “struggles for recognition”, demonstrating that the recognition of specific collective traits, including religious, is necessary to provide citizens with a sense of worth and esteem.